2021
DOI: 10.1002/suco.202000676
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on flexural performance of semi‐precast reinforced concrete one‐way slab with joint

Abstract: Semi-precast reinforced concrete (RC) slab, consisting of a precast plank with steel trusses, and a cast in-situ concrete topping, has attracted more and more attention owing to its low formwork cost and low labor work. In order to investigate the influence of joint on the slab flexural performance and the force transfer mechanism at the joint, eight semi-precast RC one-way slabs were fabricated and tested under four-point bending condition. The investigating parameters included the fundamental design part (i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The state recommends the use of high-grade concrete and high-strength steel reinforcement. High-performance concrete has the advantages of high strength, high toughness, low strain rate at high temperatures and adaptability to special environments [23][24][25][26][27][28][29]. Based on this, the new assembled beam-column node components are made of C80 high-strength concrete, which can effectively reduce the cross-sectional size of the columns and save floor space compared with ordinary-strength concrete columns, while the integral strength and stiffness of the structure will also be improved, making it easier to meet the design code requirements of "strong columns and weak beams" [30].…”
Section: Introductionmentioning
confidence: 99%
“…The state recommends the use of high-grade concrete and high-strength steel reinforcement. High-performance concrete has the advantages of high strength, high toughness, low strain rate at high temperatures and adaptability to special environments [23][24][25][26][27][28][29]. Based on this, the new assembled beam-column node components are made of C80 high-strength concrete, which can effectively reduce the cross-sectional size of the columns and save floor space compared with ordinary-strength concrete columns, while the integral strength and stiffness of the structure will also be improved, making it easier to meet the design code requirements of "strong columns and weak beams" [30].…”
Section: Introductionmentioning
confidence: 99%
“…The upper chord moment calculating formula has been recognized. Liu et al [22] studied the influence of connections on flexural performance of semi-precast slabs having steel truss on the precast portion and used finite element analysis to reproduce the experiments. The results showed that the steel truss could reduce the brittle failure and change it to a ductile failure to improve the flexural strength of the slab.…”
Section: Introductionmentioning
confidence: 99%
“…Te above-reviewed research focused on the bridge slabs having a thickness of over 200 mm, and the corresponding CIP layer was much thicker than that in the LGSs for buildings. Among the studies on the LGSs with thin thickness, Liu et al [14] adopted the connection detailing as in Figure 2(a) in the LGSs for building structures. Tey experimentally investigated the efect of slab thickness, truss element spacing within the lapping zone, and lap length of crossbar on the fexural behavior of one-way LGSs where the connections were in the middle.…”
Section: Introductionmentioning
confidence: 99%